Characteristics of hydrogen-related fatigue fracture in 2Mn-0.1C martensitic steel. (29th October 2021) - Matsumiya, Hisashi; Shibata, Akinobu; Okada, Kazuho; Tsuji, Nobuhiro
Abstract: This study investigated the hydrogen-related fatigue fracture in 2Mn-0.1C steel having a lath martensite microstructure. The presence of hydrogen significantly reduced the fatigue life. The transgranular surface was a main component in each stress range of the uncharged specimen, while the intergranular surface was frequently observed in the hydrogen-charged specimen. The crystallographic orientation analysis by electron backscattering diffraction revealed that the cracks mainly propagated along 011 planes regardless of the presence of hydrogen. Compared with the uncharged specimen, however, plastic deformation was localized near the fatigue crack in the hydrogen-charged specimen. According to the reconstructed fracture process by fracture surface topography analysis, the hydrogen-related fatigue fracture was discontinuous and composed of isolated nucleation of intergranular cracks and quasi-cleavage crack propagation initiated at the pre-existing intergranular cracks. Highlights: H-related fatigue fracture in as-quenched martensitic steel was studied. H significantly reduced the fatigue life of martensitic steel. IG surface was frequently observed in the H-charged specimen. Fatigue cracks mainly propagated along 011 planes regardless of the presence of H. IG fracture occurred in isolation, followed by QC fracture in the H-charged specimen.